2015
DOI: 10.1186/s12967-015-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis of phenotype specific stratified Indian population

Abstract: BackgroundDNA methylation and its perturbations are an established attribute to a wide spectrum of phenotypic variations and disease conditions. Indian traditional system practices personalized medicine through indigenous concept of distinctly descriptive physiological, psychological and anatomical features known as prakriti. Here we attempted to establish DNA methylation differences in these three prakriti phenotypes.MethodsFollowing structured and objective measurement of 3416 subjects, whole blood DNA of 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 56 publications
6
34
0
2
Order By: Relevance
“…This confirms an epigenetic basis for the underlying prakriti classification [134]. Such epigenetic signatures corresponding to individual prakritis may be crucial in understanding and harnessing the power of Ayurvedic medicine and ascertaining its mechanism for delivering beneficial results in health and wellness.…”
Section: Explication Of the Hypothesissupporting
confidence: 59%
“…This confirms an epigenetic basis for the underlying prakriti classification [134]. Such epigenetic signatures corresponding to individual prakritis may be crucial in understanding and harnessing the power of Ayurvedic medicine and ascertaining its mechanism for delivering beneficial results in health and wellness.…”
Section: Explication Of the Hypothesissupporting
confidence: 59%
“…Vata, Pitta and Kapha, were carried out to identify molecular differences that affect susceptibility and responses of individuals to various environmental or disease conditions. A classification method for human population, with respect to DNA methylation signatures is reported based upon traditional Ayurveda concept of prakriti 32 . In a study involving genome-wide SNP (single nucleotide polymorphism) in 262 male individuals from three different prakritis , it was found that PGM1 gene is associated with energy production.…”
Section: Current Status Of Ayurveda and Perspectives For Its Future Amentioning
confidence: 99%
“…One study conducted in a total of 3416 healthy male, non-smoking, non-alcoholic participants between the age group of 20 and 30 found significant correlations of the dominant prakriti to place of birth and BMI (p < 0.01) (Rotti et al, 2014). A genomewide single nucleotide polymorphism analysis of 262 well-classified male individuals found 52 SNPs (p < 1 x 10 -5 ) were significantly different between Prakritis, without any confounding effect of stratification, after 10 6 permutations) (Govindaraj et al, 2015).…”
Section: Papers On Clinical Investigationsmentioning
confidence: 99%
“…The main objective of these projects was to apply scientific methods in the study of Ayurvedic concepts, procedures and mechanistic basis of therapeutic effects. The work on the genomics correlates of the prakriti concept has already been alluded to (Govindaraj et al, 2015).…”
Section: Ayurvedic Biologymentioning
confidence: 99%